Comparison of chemotherapy regimens plus rituximab in adult Burkitt lymphoma: A single-arm meta-analysis - Lu, Xiaoxuan; Liu, Yu; Liu, Ruyu; Liu, Jiaxin; Yan, Xiaojing; Qian, Liren (Frontiers in Oncology, 2022)
Background and Aim Given the paucity of evidence-based treatment recommendations, the most appropriate first-line regimen for adult Burkitt lymphoma is currently undefined. We aimed to identify the optimal treatment regimen containing rituximab for adult Burkitt lymphoma patients. Methods The PubMed, Embase, Web of Science, and Cochrane databases were searched in December 2021 (10). We included all studies for the treatment of Burkitt lymphoma including rituximab. We excluded studies to those patients ages ≤14 years old and sample numbers ≤10 patients. Random effects models were used to compare different chemotherapy regimens regarding estimated 2-year overall survival (OS) rate, 2-year progression-free survival (PFS) rate, and overall response rate (ORR). Results A total of 17 studies were included in this meta-analysis and divided into four groups: CODOX-M/IVAC, DA-EPOCH, GMALL-B-ALL/NHL2002, and Hyper-CVAD. DA-EPOCH was associated with a significantly higher 2-year OS rate (0.95, 95% confidence interval [CI] 0.86-1.00). There was no significant difference in the 2-year PFS rates (0.81, 95% CI 0.76-0.85) and ORR (0.90, 95% CI 0.87-0.94) between these four treatment regimens. Conclusions The meta-analysis indicates that DA-EPOCH could be more effective in providing curative treatment for adult Burkitt lymphoma patients, especially without CNS and BM involvement considering overall survival time. Due to the types and a limited number of included studies, bias should be acknowledged and RCT needs to be performed to further identify.